Penerapan Digital Marketing sebagai Media Pemasaran Global Guna Meningkatkan Penjualan Kain Tenun Gringsing Desa Tenganan Pegringsingan Bali - Pratiwi, Kadek Sitha Ananda Laura; Luh Putu Agustini Karta, Ni; Ramanita, Ni Wayan Sovya; Aprilia, Ni Putu Nanda; Wardani, Rani Kusumo (Penerbit Goodwood, 2023)
Purpose: To analyze the affect of digital marketing strategies on increasing sales of Gringsing weaving products and the obstacles faced by business actors in implementing digital marketing are also identified so that the implementation of the strategy can run optimally. Method: The research methodology used was descriptive with a qualitative approach. The type of data used primary data from which researchers collected data through interviews. Result: The results of the discussion is that the attempt of applicating digital marketing has apositive impact on the sales of Gringsing weaving products. Digital marketing strategies, including the use of social media, online stores, and creative content, can increase brand visibility, reach global markets, and attract consumers. However, Gringsing weaving business actors need to overcome several obstacles, including lack of knowledge and skills in managing digital platforms, and limited human resources. Contribution: over all this research was in strengthen the brand image of Gringsing Weave in Bali. Limiation: The limitation of this research is focus on digital marketing, need more deep research with regard to digital marketing.